High-mass star-forming cloud G0.38+0.04 in the Galactic center dust ridge contains H2CO and SiO masers - Ginsburg, Adam; Kruijssen, Diederik (Astronomy and astrophysics, 2015)
We have discovered a new H2CO (formaldehyde) 1 1,0 −1 1,1 4.82966 GHz maser in Galactic center Cloud C, G0.38+0.04. At the time of acceptance, this is the eighth region to contain an H2CO maser detected in the Galaxy. Cloud C is one of only two sites of confirmed high-mass star formation along the Galactic center ridge, affirming that H2CO masers are exclusively associated with high-mass star formation. This discovery led us to search for other masers, among which we found new SiO vibrationally excited masers, making this the fourth star-forming region in the Galaxy to exhibit SiO maser emission. Cloud C is also a known source of CH3OH Class-II and OH maser emission. There are now two known regions that contain both SiO and H2CO masers in the CMZ, compared to two SiO and six H2CO in the Galactic disk, while there is a relative dearth of H2O and CH3OH Class-II masers in the CMZ. SiO and H2CO masers may be preferentially excited in the CMZ, perhaps because of higher gas-phase abundances from grain destruction and heating, or alternatively H2O and CH3OH maser formation may be suppressed in the CMZ. In any case, Cloud C is a new testing ground for understanding maser excitation conditions.